Loss of TaIRX9b gene function in wheat decreases chain length and amount of arabinoxylan in grain but increases cross‐linking. Issue 11 (17th May 2020) - Pellny, Till K.; Patil, Archana; Wood, Abigail J.; Freeman, Jackie; Halsey, Kirstie; Plummer, Amy; Kosik, Ondrej; Temple, Henry; Collins, Joel D.; Dupree, Paul; Berry, Simon; Shewry, Peter R.; et al.
Summary: Wheat contains abundant xylan in cell walls of all tissues, but in endosperm, there is an unusual form of xylan substituted only by arabinose (arabinoxylan; AX) that has long chains and low levels of feruloylation, a fraction of which is extractable in water (WE‐AX). WE‐AX acts as soluble dietary fibre but also gives rise to viscous extracts from grain, a detrimental trait for some non‐food uses of wheat. Here, we show that a glycosyl transferase family 43 wheat gene abundantly expressed in endosperm complements the Arabidopsis irx9 mutant and so name the three homoeologous genes TaIRX9b. We generated wheat lines with a constitutive knockout of TaIRX9b by stacking loss‐of‐function alleles for these homeologues from a mutagenized hexaploid wheat population resulting in decreases in grain extract viscosity of 50%–80%. The amount and chain length of WE‐AX molecules from grain of these triple‐stack lines was decreased accounting for the changes in extract viscosity. Imaging of immature wheat grain sections of triple‐stacks showed abolition of immunolabelling in endosperm with LM11 antibody that recognizes epitopes in AX, but also showed apparently normal cell size and shape in all cell types, including endosperm. We identified differentially expressed genes from endosperm of triple‐stacks suggesting that compensatory changes occur to maintain this endosperm cell wall integrity. Consistent with this, we observed increased ferulate dimerization and increased cross‐linking of WE‐AX molecules in triple‐stacks. These novel wheat lines lacking functional TaIRX9b therefore provide insight into control of wheat endosperm cell walls.